Autodesk Inventor 2014 and Inventor LT 2014 : essentials - Tremblay, Thom, 1967- (Sybex, 2013)
Quickly learn essential inventor tools and techniques This full-color Autodesk Official Press guide will help you quickly learn the powerful manufacturing software's core features and functions. Thom Tremblay, an Autodesk Certified Instructor, uses concise, straightforward explanations and real-world, hands-on exercises to help you become productive with Inventor. Full-color screenshots illustrate tutorial steps, and chapters conclude with a related and more open-ended project to further reinforce the chapter's lessons. Based on the very real-world task of designing tools and a.